The Role and Effectiveness of Digital Technologies in Developing Future Teachers'metacompetence (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article is devoted to the theoretical consideration of the phenomenon of smart technologies in modern education from the standpoint of the development of universal and professional competencies. The process of teaching students at a university involves turning to innovations, since the use of new technologies significantly expands the boundaries of both teaching and acquiring knowledge, and applying existing skills in practical activities.